A Qualitative Exploration of Aged-Care Residents’ Everyday Music Listening Practices and How These May Support Psychosocial Well-Being - Krause, Amanda E.; Davidson, Jane W. (Frontiers in Psychology, 2021)
Strategies to support the psychosocial well-being of older adults living in aged-care are needed; and evidence points towards music listening as an effective, non-pharmacological tool with many benefits to quality of life and well-being. Yet the everyday listening practices (and their associated specific psychosocial benefits) of older adults living in residential aged-care remain under-researched. The current study explored older adults’ experiences of music listening in their daily lives while living in residential aged-care and considered how music listening might support their well-being. Specifically, what might go into autonomous listening activities? Thirty-two Australian residents (aged 73-98) living in two Australian care facilities participated in semi-structured interviews. The results of a qualitative thematic analysis revealed three themes pertaining to “previous music experiences and interest”, “current music listening”, and “barriers to listening”. While an interest in and access to music did not necessarily result in everyday listening practices, of those participants who did listen to music, perceived benefits included outcomes such as entertainment, enjoyment, relaxation, and mood regulation. Drawing on Ruud’s notion of music as a “cultural immunogen” supporting well-being and Self-Determination Theory, theoretical implications of the findings are addressed, relating to how to create and support music activities in aged-care facilities so that they are engaging, meaningful, and promote emotional regulation, community, and well-being.